ESG, ASSET QUALITY, AND FINANCIAL PERFORMANCE: EVIDENCE FROM THE INDONESIAN MANUFACTURING SECTOR - Maria Natalia; Yuliana Gunawan; Imelda Yunita (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Analyzing the effect of interaction between ESG and asset quality on the 2019-2023 financial performance from manufacturing firm indexed on Indonesia Stock Exchange is the goal of this research. Firms published annual reports are the source for research data. If the data were unavailable on the IDX website, the researchers retrieved it from the companies’ official websites. The findings exhibit that there is no significant effect on ESG interaction with financial performance, as measured by ROA, while asset quality, measured by the quick ratio, positively affects financial performance. Contribution made by offering further insight of the interaction between ESG practices and financial performance in manufacturing firms indexed on the IDX during the 2019–2023 period. The interaction among ESG and financial performance has been explored by previous studies, but most studies have focused on global firms or broader sectors. By focusing on Indonesia’s manufacturing sector, this study provides empirical insights into how ESG factors interact with asset quality and financial performance in an emerging market context where ESG regulations are still evolving and implementation challenges persist. Thus, this research contributes to the literature by addressing a significant gap in ESG studies, which have predominantly examined developed markets or boarder sectors.